2008
DOI: 10.1080/02791072.2008.10400632
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Effects of Formaldehyde Use

Abstract: This study compared five individuals who intentionally ingested formaldehyde (possibly laced with PCP) in marijuana cigarettes to a control group on measures of cognitive ability. Formaldehyde, a major component in embalming fluid, is legal to purchase and possess and has become popular due to its euphoric properties. In significant doses, the chemical is a neurotoxin. The effects of inadvertent exposure are fairly well known, but the effects of intentional ingestion have only recently been investigated. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…A number of publications make attempt to correlate work exposure to formaldehyde with cancer, including cutaneous, nasopharyngeal, lymphatic, and hematopoietic malignancies found in embalmers and funeral directors (Coggon et al, 1984; Hayes et al, 1990; Hauptmann et al, 2004, 2009; Dreyfuss, 2010; Goldstein, 2011). Additional irritating (Muzi et al, 2004; Takahashi et al, 2007; Viegas et al, 2010; Wolkoff and Nielsen, 2010), cell proliferation altering (Hester et al, 2003), and neurophysiological effects (Marceaux et al, 2008) have been described. Phenol has shown toxic and irritating effects (Murray et al, 2007; Thullner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications make attempt to correlate work exposure to formaldehyde with cancer, including cutaneous, nasopharyngeal, lymphatic, and hematopoietic malignancies found in embalmers and funeral directors (Coggon et al, 1984; Hayes et al, 1990; Hauptmann et al, 2004, 2009; Dreyfuss, 2010; Goldstein, 2011). Additional irritating (Muzi et al, 2004; Takahashi et al, 2007; Viegas et al, 2010; Wolkoff and Nielsen, 2010), cell proliferation altering (Hester et al, 2003), and neurophysiological effects (Marceaux et al, 2008) have been described. Phenol has shown toxic and irritating effects (Murray et al, 2007; Thullner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both epidemiological and animal studies have shown that overload of exogenous formaldehyde is associated with impaired performance in learning, memory, and equilibrium, and even results in damage to the central nervous system [3,4] . In addition, intentional ingestion of significant doses of formaldehyde revealed a decline in the neuropsychological integrity of participants [5] .…”
Section: Introductionmentioning
confidence: 98%
“…Formaldehyde deregulates pathways of DNA synthesis and repair, and it interferes with regulation of cell proliferation (Hester et al,2003). In addition, neuropsychological effects related to formaldehyde have been described (Marceaux et al,2008). Due to the potential health effects of formaldehyde, dissection rooms in Germany have been shut down temporarily.…”
Section: Introductionmentioning
confidence: 99%